Editorial: a New Decade for European Papers - Ramses A. Wessel (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(1), III-V | Editorial | (Abstract) This Editorial opens the first issue of the 10th volume of European Papers: A Journal on Law and Integration. Established a decade ago, European Papers was founded with the aim of providing insights into the state of European integration and has rapidly established itself as one of the leading journals of European law. As the journal enters its second decade, the Editorial reflects on its main achievements and announces some changes for the years to come. Despite these changes, European Papers remains committed to providing in-depth assessments that collectively capture the state of European integration.